2003
DOI: 10.1046/j.1365-2966.2003.07090.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinematically quiet haloes around z   2.5 radio galaxies. Keck spectroscopy

Abstract: We present the results of the kinematic study of the extended gas in a sample of 10 high‐redshift radio galaxies (z∼ 2.5) based on high signal‐to‐noise ratio Keck II and Very Large Telescope (VLT) long‐slit spectroscopy. In addition to the typical high surface brightness kinematically perturbed regions (FWHM and velocity shifts >1000 km s−1), we find in all objects giant low surface brightness haloes that show quieter kinematics with typical emission‐line FWHM and velocity shifts of ∼several hundred km s−1. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
156
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 74 publications
(134 reference statements)
21
156
0
Order By: Relevance
“…Also, detection of extended HeII emission tracing the same velocity as Lyman-α, from the Q2222+051 nebula here, and many others (e.g. Villar-Martín et al 2003;Sánchez and Humphrey 2009), suggests the photoionized gas is in HzLAN observed directly, as HI could not backscatter the HeII line in the same way as Lyman-α. And the correlation of Humphrey et al (2007), followed by at least Q0805+046 in this sample, implies that redshifted Lyman-α usually comes (directly) from the near side of the nebulae.…”
Section: Kinematics Of the Giant Nebulaementioning
confidence: 93%
See 4 more Smart Citations
“…Also, detection of extended HeII emission tracing the same velocity as Lyman-α, from the Q2222+051 nebula here, and many others (e.g. Villar-Martín et al 2003;Sánchez and Humphrey 2009), suggests the photoionized gas is in HzLAN observed directly, as HI could not backscatter the HeII line in the same way as Lyman-α. And the correlation of Humphrey et al (2007), followed by at least Q0805+046 in this sample, implies that redshifted Lyman-α usually comes (directly) from the near side of the nebulae.…”
Section: Kinematics Of the Giant Nebulaementioning
confidence: 93%
“…However, whereas almost all of the radio galaxy nebulae in Villar-Martín et al (2003 and Humphrey et al (2007) show substantial velocity gradients (shears), amounting to ∆(v) = 200-770 km s −1 across the nebular diameter, our 5 RL-QSO nebulae have much flatter velocity profiles (Fig 14). Neither do we find examples of nebulae with more redshifted centres (like Q1425+606 and MRC 1558-003), although such an effect (if limited to a small central area) might have been hidden within the much stronger broad-line emission from the QSOs.…”
Section: Kinematics Of the Giant Nebulaementioning
confidence: 99%
See 3 more Smart Citations